The Diversity of Tropical Orchids of South Papua - Verena Agustini; Suharyanto Suharyanto; Suharno Suharno; Lisiard Dimara; Chris D. Sembay (Jurusan Biologi FMIPA Universitas Cenderawasih, 2013)
Papua is an area with very wide range, from lowland with altitude 0 m to highland area with 4730 m above sea level. Orchids species constitute the greater part of orchids diversity, which can grow on the bare branches of tall trees, or embedded in moss dripping in wet and cool mountain forests, as well as in the eternal shade of tropical rain forest. Numerous plants world-wide are threatened with extinction because of degradation or destruction of their habitat. Orchids are among the most threatened plants of all, especially when pressure from dealers and collectors aggravales the problems. South Papua is a lowland area with the elevation around 0-7 m above sea level, temperature 23-300 C, and 1500 m rainfall per year. The aims of these investigations were to explore the diversity of tropical orchids in South Papua. The exploration and collection were done in Asmat, Boven Digul, Mappi, and Merauke. The study found 22 genera and 75 species, mostly are epiphytic. Key words: orchids, exploration, diversity, South Papua.